2013
DOI: 10.5588/ijtld.12.0279
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic drug monitoring in the treatment of tuberculosis: a retrospective analysis

Abstract: In this population with high rates of treatment failure and acquired resistance, we demonstrate that most patients had low drug levels. Prospective studies are required to examine the relationship between drug levels and clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…The study showed that 50% to 60% of the patients had low concentrations of INH and RMP (12). Another study, conducted in Canada, showed that serum levels of INH and RMP were low in 76.6% and 68.4% of the patients, respectively, and that five patients with ADR showed low levels of at least one drug (13). Because TDM was performed in small numbers of selected patients with comorbidities or slow treatment responses, these studies did not clearly demonstrate the effect of low drug levels on treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study showed that 50% to 60% of the patients had low concentrations of INH and RMP (12). Another study, conducted in Canada, showed that serum levels of INH and RMP were low in 76.6% and 68.4% of the patients, respectively, and that five patients with ADR showed low levels of at least one drug (13). Because TDM was performed in small numbers of selected patients with comorbidities or slow treatment responses, these studies did not clearly demonstrate the effect of low drug levels on treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies tried to evaluate the effect of anti-TB drug concentrations on treatment outcomes (3,(12)(13)(14). One study performed in the United States included 42 patients with slow responses to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…TDM has been shown to be beneficial in the treatment of TB (14)(15)(16)(17)(18)(19). Additionally, several studies have shown that TB drug concentrations lower than the expected range are a risk factor for treatment failure (20)(21)(22)(23).…”
mentioning
confidence: 99%
“…However, ineffective drug therapy due to suboptimal drug dosages likely contributes to the high risk of death (6,7,10) or relapse after treatment (5,11). Clinical studies in adults with TB have shown that low plasma antituberculosis (anti-TB) drug concentrations are associated with a delayed treatment response (12,13) or risk of treatment failure (14)(15)(16). In particular, low plasma exposure to the rifamycins in the setting of intermittent therapy in HIV-infected patients with TB has been associated with treatment failure and emergence of rifampin resistance (16)(17)(18).…”
mentioning
confidence: 99%